High-Low Impact Exercise Program Including Pelvic Floor Muscle Exercises Improves Pelvic Floor Muscle Function in Healthy Pregnant Women – A Randomized Control Trial - Szumilewicz, Anna; Dornowski, Marcin; Piernicka, Magdalena; Worska, Aneta; Kuchta, Agnieszka; Kortas, Jakub; Błudnicka, Monika; Radzimiński, Łukasz; Jastrzębski, Zbigniew (Frontiers in Physiology, 2019)
Background: Pregnancy and high-impact activity are considered as risk factors for pelvic floor dysfunctions, including urinary incontinence. Aims: To investigate whether a structured exercise program including high-low impact aerobics and supported by pelvic floor muscle exercises improves the neuromuscular activity of pelvic floor and doesn’t reduce the quality of life in terms of urinary incontinence in healthy pregnant women. Methods: It was a randomized control trial among 97 Caucasian healthy nulliparas in uncomplicated pregnancy (age 30 ± 4 years, 21 ± 5 week of gestation; mean ± SD). Women were assessed for pelvic floor muscle functions with surface electromyography (EMG) using vaginal probes and with the Incontinence Impact Questionnaire (IIQ). Only women able to contract pelvic floor muscles and with good quality of life based on IIQ were included for the study. 70 women in the experimental group took part in supervised exercise program including high-low impact aerobics and pelvic floor muscle exercises, three times a week. 27 controls didn’t get any exercise intervention. After six weeks both groups were re-tested with EMG and IIQ. Post-pre exercise program changes in each group were analyzed using a repeated-measures ANOVA. Results: Women in the experimental group improved the neuromuscular activity of pelvic floor in some motor tasks without any adverse outcomes of the intervention. After exercise program in the experimental group we observed significantly higher EMG amplitude in pelvic floor muscles during 3-second contractions (p=0.014). We also noticed a beneficial trend in the increase of neuromuscular activity during 10- and 60-second contractions, but the changes were not statistically significant. The exercising women substantially improved the ability of relaxation following 3- and 10-second contractions (p=0.013 and p<0.001). In controls we reported no statistically significant improvement in either of the motor tasks. All study participants maintain good quality of life related to urinary incontinence. Conclusions: Exercise including high-low impact aerobics and supported by pelvic floor muscle exercises should be recommended for pregnant women. Especially among those who were accustomed to higher exercise intensity before pregnancy. Nevertheless, these recommendations can be directed to continent women who can properly contract pelvic floor muscles. ISRCTN. DOI 10.1186/ISRCTN92265528